Membangun karakter religius melalui peningkatan kualitas pendidikan dan pemahaman al-qur’an di tpq dusun pohbener desa gondowangi - audzillah, mohammad mu’zi masyfa; Izzati, Nurul Fatikhah R; Kamila, Ratu Yasmin (Maliki Interdisciplinary Journal, 2025)
The Qur’anic Education Park (TPQ) plays an important role in shaping children’s religious character through learning Qur’anic values. This research aims to evaluate and develop learning methods at TPQ Pohbener Hamlet, Gondowangi Village, using the Participatory Action Research (PAR) method with interviews and observations. KKM UIN Malang students play an active role in providing assistance, such as the Jibril method, teaching hijaiyah letters, makharijul letters, reading laws, and prayer practices. The results show an increase in students’ interest in learning and skills, although challenges such as limited parental time remain. Collaboration between the community and educational institutions is very important to build a religious generation . This finding shows that the success of the learning program at TPQ is highly dependent on the synergy between teachers, student mentors, parents, and the local community. Good collaboration between formal and non-formal educational institutions is the key to building a young generation that is religious, has good morals, and is ready to face the challenges of the times. Therefore, the sustainability of the Qur’anic character development program needs to receive continuous support from various parties, including the government, community leaders, and educational institutions.